2009
DOI: 10.1073/pnas.0809613106
|View full text |Cite
|
Sign up to set email alerts
|

The role of the dioxin-responsive element cluster between the Cyp1a1 and Cyp1a2 loci in aryl hydrocarbon receptor biology

Abstract: The aryl hydrocarbon receptor (AHR) plays a central role in 2,3,7,8-tetrachlorodibenzo-p-dioxin (dioxin) hepatotoxicity, regulation of xenobiotic metabolism, and hepatovascular development. Each of these processes appears to be dependent on binding of the AHR to dioxin-responsive elements (DREs) within the genome. The Cyp1a1 and Cyp1a2 loci represent linked genes thought to play important roles in AHR biology. In the mouse, 8 DREs are located in the 14-kb intergenic region between the Cyp1a1 and Cyp1a2 genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 53 publications
6
79
0
1
Order By: Relevance
“…In support of this assumption, kynurenine (Kyn), a major metabolic intermediate of IDO1-catalyzed tryptophan, was strikingly upregulated in IFN-β-treated B16 or A375 TRCs ( Figure 3B). Kyn is known to be an endogenous ligand for AhR (35), a critical cytoplasmic transcription factor, which translocates into the nucleus upon activation and regulates gene expression through binding to a specific DNA sequence called dioxin-responsive element (DRE) (36). In line with the increased level of Kyn, enhanced transcription activity of AhR in IFN-β-treated B16 or A375 TRCs was observed, as demonstrated by the DRE-luciferase assay ( Figure 3C).…”
Section: Ifn-β Treatment Induces Stem Cell-like Melanoma Cells Into Dsupporting
confidence: 52%
“…In support of this assumption, kynurenine (Kyn), a major metabolic intermediate of IDO1-catalyzed tryptophan, was strikingly upregulated in IFN-β-treated B16 or A375 TRCs ( Figure 3B). Kyn is known to be an endogenous ligand for AhR (35), a critical cytoplasmic transcription factor, which translocates into the nucleus upon activation and regulates gene expression through binding to a specific DNA sequence called dioxin-responsive element (DRE) (36). In line with the increased level of Kyn, enhanced transcription activity of AhR in IFN-β-treated B16 or A375 TRCs was observed, as demonstrated by the DRE-luciferase assay ( Figure 3C).…”
Section: Ifn-β Treatment Induces Stem Cell-like Melanoma Cells Into Dsupporting
confidence: 52%
“…Furthermore, the TCDD-activated reporter activity of m1a2-14.0/-12.5 was decreased in the presence of ␣-naphthoflavone, an AhR antagonist (data not shown). These results suggest the involvement of the region from Ϫ14 kbp to -12 kbp in the inducible transcriptional activation of the Cyp1a2 gene through an AhR-dependent pathway and are consistent with the recent study reported in gene-targeted mice (Nukaya et al, 2009b). There are 19 putative XREs in the Ϫ14-kbp 5Ј-flanking region of the Cyp1a2 gene, and m1a2-14.0/-12.5 contains 12 putative XREs ( Fig.…”
Section: Resultssupporting
confidence: 80%
“…These three XREs were found with the 5Ј-TNGCGTG-3Ј sequence, which is more stringent than the 5Ј-GCGTG-3Ј sequence and are within the region reported by Nukaya et al (2009a,b). Because mice lacking the 1.2-kbp XRE cluster region showed partial inducible transcriptional activation of Cyp1a2 (Nukaya et al, 2009b), the involvement of a repressive element for transcriptional activation in this region is suspected; the negative regulatory region for Cyp1a1 was reported to be located in the region (Gonzalez and Nebert, 1985). The regulatory region for inducible transcriptional activation of the mouse Cyp1a1 gene was reported previously (Gonzalez and Nebert, 1985;Neuhold et al, 1986Neuhold et al, , 1989Denison et al, 1989;Fisher et al, 1990), which suggests that a single XRE was not sufficient for the inducible activation of Cyp1a1, and the regulatory region was found to contain sequences complementary to XRE13, XRE14, and XRE15 of the Cyp1a2 gene.…”
Section: Resultsmentioning
confidence: 99%
“…In mouse, seven out of eight DREs are located 1.4 kb upstream of the CYP1A1 transcriptional start site and 12.6 kb upstream of the CYP1A2 start site. Furthermore, the DREs regulate both CYP1A1 and CYP1A2 expression in vivo and these two gene products do not cause many common dioxin-induced toxic endpoints (Nukaya et al, 2009). For these reasons, the activity of these response elements further enhances the evidence for considerable diversity in vertebrate CYP1A regulation (Lewis et al, 2004).…”
Section: Induction Of Cyp1amentioning
confidence: 99%